Mapeamento de competências dos enfermeiros no âmbito da saúde global e internacional em região de fronteira - Scherer, Karina Emilia dos Santos (2022)
The current scenario of globalization affects the world's population in socioeconomic, cultural, and political terms. Health issues go beyond borders, with regard to migration, disasters, diseases, and environmental problems. In this context, the organizations and actions of health services in border regions are constantly evolving, resulting in a greater demand for efficiency and quality at all levels of care in the context of global health. Thus, the role of the nurse in this scenario stands out, as the main protagonist in the systematization of care, committed to clinical and managerial nursing practice. The objective of the current research was to carry out the mapping of competences for global health with the population of 133 nurses who work in public health care in a border municipality. This descriptive exploratory research, with a quantitative approach was carried out in two steps. Step 1) Literature review through a scoping review, outlined from the recommendations of the Joanna Briggs Institute. Step 2) Field research carried out in three phases: 1st, document analysis; 2nd, application of a questionnaire from the Brazilian version of the Questionnaire on Essential Basic Competences in Global Health, comprising 30 competencies described in six domains; and the 3rd and final phase, identification of gaps between the competences found. Quantitative data were analyzed using Minitab software. For the analysis of the statistical data, Cronbach's Alpha and descriptive statistics were used, and the analysis of the open question was carried out through Bardin's content analysis. The results show that all domains presented an alpha greater than 0.70, demonstrating good reliability of the questionnaire in the studied population, with the domains social determinants and health environments and globalization of health and health care presenting alpha values > 0.90. However, weaknesses were identified in the skills Global Impact of Diseases, and Health as a human right and a resource for development, in addition to difficulties encountered with the language, lack of knowledge of the rights of border populations, and xenophobia. Health problems transcend international barriers and this situation becomes even clearer in border cities like Foz do Iguaçu, requiring knowledge of global issues related to culture, epidemics, communicable and non-communicable diseases, epidemiology, humanitarian actions, and emergency situations.